Analisis Bentuk Penyajian Tari Fanari Niowalu pada Acara Falöwa di Kecamatan Idanögawo - Harefa, Mega Suryawan; Malarsih, Malarsih; Nugrahani, Rahina (Ideas Publishing, 2024)
The fanari niowalu dance is a traditional dance which is one of the sacred dances in wedding customs which is only danced by niowalu at the falöwa which symbolizes that Niowalu is ready to get married and welcomes the extended family of the marafule (groom), guests and the community who come was at the falöwa event. The purpose of writing this article is to analyze the form of presentation of the fanari niowalu dance using qualitative research methods with an ethnochoreological approach that describes existing problems. This dance is danced at weddings where the dance is started by the mothers of the bride and groom and then continued by the two girls and niowalu to dance together with traditional Nias musical instruments consisting of göndra, garamba, and faritia.